Curiosity and digital communication of mildly autistic students with realistic mathematic learning approach using the Quizizz - Nuraida, Elis Muslimah; Santri, Diah Dwi; Wulandari, Chintia Putri; Marini, Riri (Universitas Sarjanawiyata Tamansiswa, 2025)
Communication is a key factor in the exchange of emotions and information during interactions. In fact, in schools, most children with disabilities, such as autism, experience significant verbal communication difficulties. Only about 45% of students with autism can communicate verbally, while 55% still rely on nonverbal communication or assistance. Additionally, students with autism have limitations in expressing their emotions, making them highly prone to tantrums. This is one of the reasons why teachers in schools often hesitate to provide digital media to students with autism. Digital communication is also a form of communication skills, but it is based on Information and Communication Technology (ICT) to facilitate relationships and interactions with others. This study aims to explore how the curiosity and digital communication skills of students with autism can be enhanced through a realistic mathematics learning approach using Quizizz. This research employs a descriptive qualitative method, utilizing data collection techniques such as interviews, observations, and documentation. The findings, based on observational instruments conducted over three sessions, indicate that students' digital communication skills improved in each session, increasing from 44% to over 80%. Furthermore, the use of Quizizz also contributed to enhancing the verbal communication skills of students with autism. Through Quizizz, students with autism were able to practice self-expression, select answers, and even interact with their peers in game mode. This research provides valuable insights into how students with moderate autism respond to realistic and interactive mathematics learning while helping educators better understand their special needs and develop more effective teaching strategies.